Mekanisme Penetapan Harga Jual dalam Tinjauan Ekonomi Islam Terhadap Usaha Toko Serba 35 Fauzi Collection Sintang - Melja Pusarti; Tehedi; Deni Irawan (CBJIS: Cross-Border Journal of Islamic Studies, 2024)
This research departs from the phenomenon of pricing carried out by the fauzi collection shop in Sintang which sets a selling price of 35 thousand. This shop is experiencing very rapid development. The existence of this shop has a very good impact so that it can be felt by the middle to lower economic community. Thus, this journal has a research focus, namely: (1) How is the mechanism for determining the selling price at the Sintag collection fauzi shop? (2) How is the Islamic economic review of the mechanism for determining the selling price? (3) What is the impact of setting the selling price. This research uses a qualitative descriptive analytical approach and type of field study research. Data collection techniques through interviews, observation and documentation. Data analysis includes data reduction, data display, and verification / conclusion drawing. The results of the discussion show that the mechanism for determining the selling price at the all-round shop 35 fauzi collection Sintang is based on capital, employee wages, rental space, electricity costs, and distribution costs. In setting prices, there are six procedures carried out by the all-round shop 35 fauzi collection Sintang, namely choosing objectives in pricing, determining demand, estimating costs, analyzing costs, prices and competitor offers, choosing pricing methods, setting the final price. The type of strategy used is competition based pricing / competitive pricing strategy. The Islamic economic review of the selling price setting mechanism carried out by the owner of the all-round shop 35 fauzi collection Sintang is in accordance with Islamic economics, prices do not harm sellers and buyers. The price is in accordance with the benefits of the goods provided. The impact of pricing carried out by the owner of the all-round shop 35 fauzi collection Sintang is a positive impact that can be felt by the middle to lower class people.